Gerd van Riel, Plato’s Gods (Burlington, Vt.: Ashgate, 2013); vii and 137 pp.; 153.00 (cloth), 50.95 (paper), 45.86 (ebook). - Cusack, Carole M. (Pomegranate, 2018)
Gerd van Riel, Plato’s Gods (Burlington, Vt.: Ashgate, 2013); vii and 137 pp.; 153.00 (cloth), 50.95 (paper), 45.86 (ebook).